BENTUK PERMINTAAN SOPAN DALAM BAHASA INGGRIS DAN BAHASA BOLANGO SUATU ANALISIS KONTRASTIF - KOMBU, NOVITA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT Â This skripsi is entitledÂ â€Bentuk Permintaan Yang Sopan dalam Bahasa Inggris dan Bahasa Bolango : Suatu Analisis Kontrastifâ€. The problems in this research is whatÂ are the forms of polite request in English and Bolango Language and, the similarities and difference between the two language. The research to be answered are the forms of polite request in English and Bolango language. In terms of methodology, this study the data collected through library research and field studies using descriptive method and contrastive analysis. The data of both languages are analyzed based on the theories of Leech. The result of the research shows that English and Bolango languages have similarities in the forms of polite request. This similarities, for example, can be found in the polite signer of each language. The polite signer of both languages have the same meaning. English and Bolango language have sentence patterns which are used to request the hearer to do something what speaker wants. Polite request forms of English and Bolango language have command,order,and teasing meaning for the hearer to do something. The differences of the polite request of the two language lie in their forms. Another difference is polite request pattern as an invitation to the hearer to do something with the speaker. Was only found in English. Â Key words: The form of polite request, English and Bolangolanguage,Contrastive analysis